The impact of retirement on physical, mental health and wellbeing. (30th September 2020) - Odone, A; Frascella, B; Vigezzi, G; Gaetti, G; Gianfredi, V
Abstract: Population ageing presents both challenges and opportunities for societies around the world. Increasing statutory retirement age and limiting exits to early retirement are frequent policy responses to population ageing, but this is unlikely to have the desired impact if the complex relationships that link work, retirement and health remains unknown. In this context, we designed and are currently conducting the multi-partner project on pension reforms and spatial-temporal patterns in healthy ageing, funded by Fondazione Cariplo. The project involves a multi-disciplinary research team from University Vita-Salute San Raffaele, Bocconi University and the Unit of Epidemiology of the Regional Health Service of ASL TO3. In this first presentation we will first describe the project design, its general aim and specific objectives, then we will present a proposed conceptual framework on the association between retirement and health and its determinants. The framework is the first deliverable of the project and is the results of a comprehensive review of the available evidence and consultation with experts in the field. In particular we conducted a scoping review to retrieve, pool and critically appraise the relevant evidence on the impact of retirement and transition to retirement on physical and mental health and their determinants. We summarized the evidence collected in a conceptual framework that attempt to quantify how health and retirement are bi-directionally linked, how health is central to the timing of retirement, how labor-associated determinants condition employment cessation, how and retirement have varying effects on risk factors for physical and mental health and the role of confounding factors and mediators. Towards the end of the presentation we will outline an extensive stakeholder mapping carried out for the purposes of the project at the national and European level